Implementation of EU Acts in the Czech Parliament: A Slow and Laborious Quest with an Uncertain Outcome - Říha Michal (Wroclaw Review of Law, Administration and Economics)
The article focuses on the statutory implementation practice of EU legislation in the Czech Republic based on statistical evidence. The main focus is a comparison of the length of the legislative procedure in the Parliament from 2010–2021, i.e. three election periods of the Chamber of Deputies, which is the dominant body of law-making in the Czech Republic. In conclusion, the author describes an unusually lengthy implementation process and analyses possible reasons for one of the worst transposition-on-time results within the EU. However, he refutes the claim that the transposition deficit is mostly caused by the Parliament.